Antivirus and antibacterial filters for face masks based on silver quantum dots - Jokanović, Vukoman; Zdravković, Nemanja; Petrović, Božana; Živković, Marija; Biočanin, Vladimir; Aleksić, Ema; Milutinović, Jovana; Petrović, Tamaš (Vojnosanitetski pregled, 2024)
Background/Aim. Available face masks, used to protect the respiratory system from various types of pathogens, show unsatisfactory efficiency because the size of viruses like severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is much smaller than the void spaces in these masks. Difficult breathing through some masks quickly tires out, which makes ordinary people avoid wearing them. These facts suggest that a new strategy is desirable for designing protective face masks. The aim of the study was to present new filters for face masks to protect people exposed to high concentrations of bacteria and viruses, particularly SARS-CoV-2. Methods. Filters for these masks were manufactured of dense cotton fabric impregnated with silver quantum dots. The filters were characterized by scanning electron microscopy and ion-coupled plasma mass spectrometry. Wettability properties were determined by measuring contact angles with water, and a color fastness test was performed. Antibacterial assay was performed using Staphylococcus (S.) aureus. Viability quantitative polymerase chain reaction (qPCR) for virus integrity assay and reverse transcription qPCR (RT-qPCR) assay were used for antiviral activity assessment. Results. In vitro assays showed extremely high efficiency of these filters in destroying S. aureus and SARS-CoV-2 virus. The filters also showed high safety and easy breathing possibilities. Conclusion. The high efficiency of these masks against SARS-CoV-2 has been demonstrated through numerous tests, and they have been approved as anti-SARS-CoV-2 masks for the first time in the world. In the meantime, this solution has been applied in practice, and the data obtained about that are very encouraging.